Features of sociological research to culture of a healthy way of life of minors - Shimanovskyi, Mark (Professional Pedagogics, 2012)
The article deals with theoretical problems of sociological analysis that occur during an ascertaining experiment in pedagogy. Range of research problems in the area of intimate relationships is emphasized. It is especially necessary due to problems connected with the spread of sexually transmitted diseases, HIV/AIDS, underage pregnancies and abortions.
Keywords: sociology studies; linguistics; intimate relations; minors; sexually transmitted diseases; HIV/AIDS; underage pregnancies and abortions